Empowerment of Women and Marital Harmony under Vision 2030: A Descriptive Study on the Empowerment of Women and Marital Harmony in the Kingdom of Saudi Arabia from the Perspective of Vision 2030 - Almaliki, Safiah Mubarak (Journal of Humanities & Social Sciences, 2024)
Vision 2030 aims to appreciate and enhance the role of Saudi women and view them with a positive and optimistic outlook, as they have proven the importance of their distinctive role in various aspects of life. The vision focused on supporting Saudi women as a vital part of building the nation, and this study aims to identify the impact of women’s empowerment on marital compatibility. The study adopted the quantitative descriptive approach using an electronic questionnaire on a random sample of 242 individuals from women and men in Saudi society. The study included four main dimensions that affect marital compatibility, which are: personal status laws, the guardianship system, the women’s rights law, and women driving cars. Based on the results of the study, focus should be placed on starting to empower women from within their home and family. Marital compatibility is mainly due to harmony between spouses, and the region of residence and tribe may be influential factors. The study also showed women's belief in the importance of empowering them in various fields, and this is considered a positive factor that contributes to improving women's status. Also, employed women seem more open and interested, and 24% of the participants in the study described themselves as housewives who do not need to look for work. Therefore, the study recommends increasing awareness among Saudi women about the importance of entering the labor market if their family circumstances allow it. Encouraging women to pursue careers in traditionally male-dominated fields.
Keywords: Women's Empowerment; Marital Compatibility; Saudi Women's Rights